A human rights approach to combating corruption in Africa : appraising the AU Convention using Nigeria and South Africa - Matusse, Angelo (University of Pretoria, 2006)
Prepared under the supervision of Dr. Angelo Matusse at the Faculdade de Direito, Universidade Eduardo Mondlane, Maputo, Mocambique